1970
DOI: 10.1136/bmj.4.5732.406
|View full text |Cite
|
Sign up to set email alerts
|

Endocrine Function in Male and Female Homosexuals

Abstract: MEDIAof measurements indicate that for any particular fundal level there is up to eight weeks' variation in gestational age. In practice, therefore, the clinical detection of a baby "large for dates" or "small for dates" necessitates at least four to six weeks' difference between the traditional level of the fundus and the fundal height observed.No standard rate of uterine growth was discovered in this study and sometimes no detectable increase in the level of the fundus occurred throughout four weeks of pregn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
12
0
1

Year Published

1972
1972
2014
2014

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(16 citation statements)
references
References 14 publications
3
12
0
1
Order By: Relevance
“…Such dysfunction may explain the link between migraine and hypothalamic-regulated circadian rhythms, such as timekeeping, gonadal hormones, and cortisol secretion. Furthermore, homosexual men have a higher incidence of migraine (7.2 vs. 15.5%) (105), lower testosterone levels (106), increased suprachiasmatic nucleus volume (107), and decreased interstitial nucleus volume of the anterior hypothalamus number 3 (INAH3) compared to heterosexual men, but volumetric similarities (in the different hypothalamic nuclei) with women (108). …”
Section: Hypothalamic Role In Hormonal Regulation Of Brain Dysmetria mentioning
confidence: 99%
“…Such dysfunction may explain the link between migraine and hypothalamic-regulated circadian rhythms, such as timekeeping, gonadal hormones, and cortisol secretion. Furthermore, homosexual men have a higher incidence of migraine (7.2 vs. 15.5%) (105), lower testosterone levels (106), increased suprachiasmatic nucleus volume (107), and decreased interstitial nucleus volume of the anterior hypothalamus number 3 (INAH3) compared to heterosexual men, but volumetric similarities (in the different hypothalamic nuclei) with women (108). …”
Section: Hypothalamic Role In Hormonal Regulation Of Brain Dysmetria mentioning
confidence: 99%
“…A previous study by Margolese (1970) showed that healthy adult males excreted androsterone and etiocholanolone in ratios that clearly discriminated between heterosexual and homosexual subjects. This was followed by a study by Lorraine (1970) who found low urinary testosterone in two homosexual males and raised urinary itestosterone in four homosexual females. The idea that changes in endocrine function might contribute to the genesis of homosexuality in humans was then given further impetus by Kolodny et al (1971) who showed that plasma testosterone levels of a homosexual group were significantly lower than those of a control group.…”
Section: Introductionmentioning
confidence: 93%
“…The prediction was that lesbians would have more masculine patterns of hormones than would heterosexual women. Several small studies found differences between lesbians and heterosexual women (Gartrell, Loriaux, & Chase, 1977;Loraine, Adamopoulos, Kirkham, Ismail, & Dove, 1971;Loraine, Ismail, Adamopoulos, & Dove, 1970). In contrast, three more recent studies comparing carefully matched samples of lesbians and heterosexual women failed to find significant differences on multiple hormonal measures (Dancey, 1990;Downey, Ehrhardt, Schiffman, Dyrenfurth, & Becker, 1987;Griffiths et al, 1974).…”
Section: Evaluating the Biological Research On Women's Sexual Orientamentioning
confidence: 99%